Mastering illiquidity risk management for portfolios of limited partnership funds - Cornelius, Peter 1960- (John Wiley & Sons, Ltd., 2013)
Arms investors with powerful new tools for measuring and managing the risks associated with the various illiquid asset classes With risk-free interest rates and risk premiums at record lows, many investors are turning to illiquid assets, such as real estate, private equity, infrastructure and timber, in search of superior returns and greater portfolio diversity. But as many analysts, investors and wealth managers are discovering, such investments bring with them a unique set of risks that cannot be measured by standard asset allocation models. Written by a dream team of globally renow.
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Private equity funds; Portfolio management; Risk management; Risk Management; Fonds de capital-investissement; Gestion de portefeuille; Gestion du risque; risk management; BUSINESS & ECONOMICS; Investments & Securities; Mutual Funds; BUSINESS & ECONOMICS; Finance